The nature and origins of the low surface brightness outskirts of massive, central galaxies in Subaru HSC - Jackson, Thomas M.; Pasquali, Anna; La Barbera, Francesco; More, Surhud; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2023)
We explore the stellar mass density and colour profiles of 118 low redshift, massive, central galaxies, selected to have assembled 90 per cent of their stellar mass 6 Gyr ago, finding evidence of the minor merger activity expected to be the driver behind the size growth of quiescent galaxies. We use imaging data in the g, r, i, z, y bands from the Subaru Hyper Suprime-Cam survey and perform SED fitting to construct spatially well-resolved radial profiles in colour and stellar mass surface density. Our visual morphological classification reveals that ∼42 per cent of our sample displays tidal features, similar to previous studies, ∼43 per cent of the remaining sample displays a diffuse stellar halo, and only ∼14 per cent displays no features, down to a limiting μr-band ∼ 28 mag arcsec−2. We find good agreement between the stacked colour profiles of our sample to those derived from previous studies and an expected smooth, declining stellar mass surface density profile in the central regions (< 3 Re). However, we also see a flattening of the profile (Σ* ∼ 107.5 M⊙ kpc−2) in the outskirts (up to 10 Re), which is revealed by our method of specifically targeting tidal/accretion features. We find similar levels of tidal features and behaviour in the stellar mass surface density profiles in a younger comparison sample, however, a lack of diffuse haloes. We also apply stacking techniques similar to those in previous studies, finding such procedures wash out tidal features and thereby produce smooth declining profiles. The stellar material in the outskirts contributes on average ∼1010 M⊙ or a few per cent of the total stellar mass and has similar colours to SDSS satellites of similar stellar mass.
Gesehen am 30.03.2023